2011
DOI: 10.1186/1471-2407-11-467
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for the OUTREACH trial: a randomised trial comparing delivery of cancer systemic therapy in three different settings - patient's home, GP surgery and hospital day unit

Abstract: BackgroundThe national Cancer Reform Strategy recommends delivering care closer to home whenever possible. Cancer drug treatment has traditionally been administered to patients in specialist hospital-based facilities. Technological developments mean that nowadays, most treatment can be delivered in the out-patient setting. Increasing demand, care quality improvements and patient choice have stimulated interest in delivering some treatment to patients in the community, however, formal evaluation of delivering c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
(14 reference statements)
0
4
0
1
Order By: Relevance
“…The trial had ethics committee approval and was registered as ISRCTN66219681. Full descriptions of the protocol and methods have been published previously (Corrie et al , 2011). In brief, cancer patients over 18 years of age with an ECOG performance status 0–2 and living within a 30-min drive of recruiting hospitals were eligible.…”
Section: Methodsmentioning
confidence: 99%
“…The trial had ethics committee approval and was registered as ISRCTN66219681. Full descriptions of the protocol and methods have been published previously (Corrie et al , 2011). In brief, cancer patients over 18 years of age with an ECOG performance status 0–2 and living within a 30-min drive of recruiting hospitals were eligible.…”
Section: Methodsmentioning
confidence: 99%
“…En esta línea, hasta hace unos años el tratamiento farmacológico contra la neoplasia se había administrado tradicionalmente en unidades especializadas dentro de las instalaciones hospitalarias. Pero, los avances tecnológicos y la mejora en la calidad de la atención han hecho posible que, hoy en día, la mayoría de la quimioterapia ya se pueda administrar de manera ambulatoria (4).…”
Section: Introductionunclassified
“…However, there are also studies stating the opposite of these findings and that the costs of home-based chemotherapy treatment are lower [ 29 , 35 , 38 , 42 ]. In addition to these two perspectives, two different studies conducted in the United Kingdom showed that there is no difference in cost between the hospital, outpatient, and home-based chemotherapy administration [ 22 , 43 ]. Hirtzlin and Préaubert Hayes [ 44 ], on the other hand, with a different perspective from all of these, stated that the cost of outpatient chemotherapy treatment is higher than the cost of home-based treatment.…”
Section: Discussionmentioning
confidence: 99%